Perilaku Komunikasi pada Masyarakat Cyberspace : (Netnografi Meme Rage Comic di Situs 1cak.com) - Muftitama, Adriansyah (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2023)
New media has significantly changed the order of the flow of human communication and information, especially to adolescent. As digital natives, they are directly part of the cyberspace culture, where most of their communication activities are carried out in the internet digitization space. This study aims to understand how the communication behavior of rage comic meme users on the 1cak.com website is viewed from two main aspects: the pattern of meme content and the categorization of meme humor. A qualitative method with a semiotic approach is used as an effort to comprehensively understand the meme communication behavior on the site. As a result, the pattern of meme content on the 1cak.com site is divided into two typical users: the up to date pattern (structured) and the random pattern (unstructured). Meanwhile, the meme humor theme category on the 1Cak website is divided into four categories: Pure-Humor; Experiences-Based Humor; Educative-Humor; and Segmented-Humor.